Functionalized Rosette Nanotubes as Novel Electron Donor Materials for Solution-Processed Organic Photovoltaics. Issue 1737 (11th February 2015) - Shuai, Liang; Parthasarathy, Venkatakrishnan; Cho, Jae-Young; Yamazaki, Takeshi; Beingessner, Rachel L.; Fenniri, Hicham
ABSTRACT: Two self-assembling twin guanine-cytosine (G∧C) hybrid molecules featuring porphyrin (TPPO-(G∧C)2 ) and oligothiophene groups (6T-(G∧C)2 ) were synthesized. In organic solution, these molecules self-assemble into one-dimensional rosette nanotubes (RNTs) featuring the porphyrin or oligiothiophene groups on the outer surface. Using a combination of imaging and spectroscopic techniques we established the structure of the TPPO-(G∧C)2 and 6T-(G∧C)2 RNTs and compared the HOMO and LUMO energy levels with PC61 BM, a well-known electron acceptor material. These studies, in combination with solid-state photoluminescence data of PC61 BM-TPPO-(G∧C)2 RNT blended thin films, indicates that these self-assembled nanomaterials have great potential as electron donor materials for solution-processed organic photovoltaics.